Penerapan Material Flow Cost Accounting (MFCA) untuk Mengidentifikasi Hidden Cost dan Meningkatkan Efisiensi Pengelolaan Limbah Perishable melalui Pendekatan Circular Economy pada Sektor Ritel Modern - Nana Nurwana; Juniati Gunawan (Masyarakat Ekonomi Syariah Bogor, 2026)
Material Flow Cost Accounting (MFCA) has been widely applied in manufacturing industries; however, its implementation in the modern retail sector, particularly for managing perishable food waste, remains limited. This study aims to analyze the application of MFCA in identifying hidden waste costs and evaluating the potential recovery of economic and environmental value from fruit and vegetable waste at PT LS, a modern retail company. A descriptive qualitative case study supported by quantitative analysis was employed using observation, interviews, and documentation of damaged goods reports, inventory records, purchasing data, sales reports, operational costs, and waste management costs. MFCA was utilized to map material flows, distinguish positive and negative products, quantify material loss, and evaluate material efficiency and economic recovery through composting activities. The findings reveal that 206 kg of organic waste with an economic value of IDR 4,279,558 was processed into 72.3 kg of compost, resulting in a material efficiency of 35.1%, material loss of approximately 65%, and an economic recovery value of IDR 361,500 (8.45%). Although the direct financial return remains relatively low, MFCA successfully exposed previously unidentified hidden costs associated with perishable waste, improved transparency in material flow information, and demonstrated that organic waste can be transformed into value-added products supporting circular economy practices. This study extends the application of MFCA beyond the manufacturing sector by providing empirical evidence that the method can enhance resource efficiency, environmental performance, and sustainable waste management in the modern retail industry.